Eden's children : [large type] a novel - Andrews, V. C. (Virginia C.) ([Eden series], 2023)
"When former teacher Paula Eden adopts Faith and Trevor, she is astounded by their natural intelligence and decides to homeschool them to nurture their brilliance. But as the years go on, Faith and Trevor itch for more independence. When Faith sets her sights on a handsome young man visiting from out of town, Paula grows increasingly desperate to preserve her small family and her plans for the children to carry on her legacy. Luckily, she has a cohort in loyal Trevor, who will do anything to please his mother, even at the risk of hurting his sister and potentially changing their lives forever."--